Prevalence, Risk Factors, and Etiology of Extubation Failure in Pediatric Patients After Cardiac Surgery - Beshish, Asaad G.; Fundora, Michael P.; Aronoff, Elizabeth; Rao, Nikita; Kelleman, Michael S.; Shaw, Fawwaz R.; Maher, Kevin O.; Wolf, Michael (Journal of Pediatric Intensive Care, 2022)
In this article, our primary objective was to investigate the prevalence and etiology of extubation failure (EF) in patients following cardiac surgery for congenital heart disease. Secondarily, we examined the association of different risk factors with EF. This was single-center retrospective study in a 27-bed cardiac intensive care unit at a quaternary children's hospital. All patients between 0 and 18 years of age who underwent congenital cardiac surgery from January 2008 to September 2019 were included. During the study period, among 8,750 surgical encounters, 257 (2.9%) failed extubation, defined as reintubation within 48 hours from extubation. EF patients were younger, smaller, more likely to have genetic syndromes, higher Society of Thoracic Surgeons and the European Association for Cardio-Thoracic Surgery (STAT) mortality scores, single-ventricle physiology, longer cardiopulmonary bypass (CPB) and cross-clamp (XC) times, longer mechanical ventilation (MV) duration, and higher mortality (p <0.05). In a univariate analysis, EF patients when compared to matched controls by age, gender, and STAT score, and genetic syndrome, particularly heterotaxy, were associated with increased odds of EF (p <0.05). In a multivariable logistic regression of the entire cohort, the presence of any genetic syndrome was associated with higher odds of EF (p <0.05). In a subgroup of neonates, a univariate analysis was performed and multivariable analysis was attempted, but both did not achieve statistical significance. In summary, EF after congenital cardiac surgery is associated with younger age, lower weight, single-ventricle physiology, longer CPB and XC times, longer duration of MV, and genetic syndromes. Patients failing extubation have increased morbidity and mortality. Recognition of these risk factors may provide clinicians the ability to identify patients at high risk allowing for timely intervention to limit adverse outcomes.
Keywords: extubation failure; congenital heart disease; cardiac surgery